Bactericidal Antibody Responses Elicited by A Meningococcal Outer Membrane Vesicle Vaccine with Over-Expressed fHbp and Genetically-Attenuated Endotoxin - Koeberling, Oliver (2008)
BACKGROUND: Outer membrane vesicle (OMV) vaccines from mutant N. meningitidis strains engineered to over-express factor H-binding protein (fHbp) elicited broadly protective serum antibody responses in mice. The vaccines investigated were not treated with detergents to avoid extracting fHbp, which is a lipoprotein. Because of their high endotoxin content, the vaccines would not be safe to administer to humans. METHODS: We prepared a native OMV vaccine from a strain engineered to over-express fHbp and in which the gene encoding LpxL1 was inactivated, which reportedly decreased endotoxin activity. RESULTS: The OMV vaccine from the mutant had similar or lower ability to induce proinflammatory cytokines by human peripheral blood mononuclear cells as a detergent-extracted wildtype OMV, and 1000- to 10,000-fold lower activity than a native wildtype OMV. In mice, the OMV vaccine from the mutant elicited higher serum bactericidal antibody responses against a panel of heterologous N. meningitidis strains than a control multicomponent recombinant protein vaccine, or a detergent-extracted OMV vaccine that previously had been demonstrated to confer protection against meningococcal disease in humans. CONCLUSIONS: The data illustrate the potential to develop a broadly immunogenic native OMV vaccine with decreased endotoxin activity that is potentially suitable for testing in humans.